Differential epigenetic regulation by blue and UV-A light reveals the key role of CsSDG36-mediated H3K4 methylation in leaf development and secondary metabolism in Camellia sinensis - Pu Wang; Hong Zhang; Yongli Yin; Yue Ge; Binrui Chen; Jing Hu; Yu Wang; Dejiang Ni; Fei Guo (Genome Biology)
Abstract Background There is a Chinese proverb that good tea comes from high mountains with clouds and mists, suggesting the important impact of environmental factors on the development and secondary metabolism in tea plants. However, the epigenetic mechanism involved is still unclear. Results High altitude results in light enhancement with a higher retention of short-wavelength light in cloudy conditions, suggesting the key role of short-wavelength light in the quality formation of tea plants. Thus, we focus on the representative short-wavelength light, blue and UV-A, and characterize plant responses in epigenome, transcriptome, leaf development, and metabolome. We profile six histone modifications under different light wavelengths and link these to leaf development and secondary metabolism, including changes in gene expression during flavonoid, theanine, caffeine, and β-carotene biosynthesis. There is higher stomatal density and thicker mesophyll tissues under blue light, with higher levels of chlorophyll components under UV-A light. The epigenome results in differential changes of stomatal density and quality components in different light conditions. We further identify crucial histone modifications in leaf development and secondary metabolism. Functional analyses suggest diverse regulations mediated by cryptochrome and phototropin in light adaptation, and we confirm the important role of CsSDG36-mediated histone H3K4 methylation. Conclusion Our results not only reveal the landscape of histone modifications, transcripts, leaf development, and metabolites from different lights in tea plants, but also provide insight into the roles of photoreceptors and epigenetic mechanisms involved in leaf development and secondary metabolism.